Swine flu and hype: a systematic review of media dramatization of the H1N1 influenza pandemic. Issue 1 (2nd January 2016) - Klemm, Celine; Das, Enny; Hartmann, Tilo
Abstract : Highly disconcerting at the time, in retrospective, the 2009 H1N1 influenza pandemic looks like much ado about nothing. As a consequence, many accused the media of having created an artificial hype or hysteria around the new virus, thus contributing to unwarranted public fear. The current paper set out to examine the validity of such accusations. We integrated empirical findings on whether the media dramatized H1N1 on a global scale through systematically reviewing prior content-analytic studies. We developed a coding scheme specifying three indicators of dramatized media coverage that – together – inform about how mass media coverage about H1N1 may amplify risk perceptions in the public: (a) the volume of media coverage, (b) the media content presented, particularly an overemphasis of threat while neglecting measures of self-protection and (c) the tone of coverage. Results show that media attention was immense, that news content stressed threat over precautionary measures, while the pattern of coverage tonality remained nebulous due to conflicting findings. The present review also revealed a critical gap in existing knowledge about the tone of media coverage on H1N1, and discusses implications for future research on dramatization of public health risks by the media.